2019
DOI: 10.5798/dicletip.574791
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto tiroiditinin trombositler üzerine sayı, büyüklük ve dağılım açısından etkisi

Abstract: Objective: The aim of our study was to investigate whether platelet indices were affected in patients with Hashimoto's thyroiditis (HT). Method: 11 patients (10 female, 1 male) with HT and 26 subjects with nodular goiters (19 female, 7 male) selected as control group were included in the study. All cases were examined for complete blood count parameters (leukocyte count, neutrophil count and percentage, lymphocyte count and percentage, platelet count, plateletcrit, platelet distribution width (PDW), and mean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…In a study conducted by Güvendi et al. , 23 PDW was elevated in patients with Hashimoto’s thyroiditis. They suggested this indicated can be used for diagnosis and follow-up of the disease.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In a study conducted by Güvendi et al. , 23 PDW was elevated in patients with Hashimoto’s thyroiditis. They suggested this indicated can be used for diagnosis and follow-up of the disease.…”
Section: Discussionmentioning
confidence: 88%
“…Bilge et al 22 found that MPV and PDW were high in patients with Hashimoto's thyroiditis and noted that these changes may be associated with inflammation and malignancy. In a study conducted by Gu¨vendi et al, 23 PDW was elevated in patients with Hashimoto's thyroiditis. They suggested this indicated can be used for diagnosis and follow-up of the disease.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations